Arabic Language Learning Based on Technology (Opportunities and Challenges in the Digital Era) - A. Rani, Samsuar; Zikriati, Zikriati; Muhammady, Aan; Syukran, Syukran; Ali, Banta (International Journal of Education, Language, and Social Science, 2023)
Technology-based Arabic language learning is an innovation that is considered effective in improving the quality of Arabic language learning in the digital era. In this article, we will discuss the opportunities and challenges of technology-based Arabic language learning. These opportunities include ease of access, flexibility of time and place, and the availability of diverse learning resources. However, there are also several challenges faced in technology-based Arabic language learning, such as uneven content quality, the need for stable internet access, and the lack of social interaction. Therefore, there is a need for efforts to overcome these challenges so that technology-based Arabic language learning can run optimally and provide optimal benefits to learners.